Interspeech 2018 2018
DOI: 10.21437/interspeech.2018-1518
|View full text |Cite
|
Sign up to set email alerts
|

Language Features for Automated Evaluation of Cognitive Behavior Psychotherapy Sessions

Abstract: Cognitive Behavior Therapy (CBT) is a psychotherapy treatment that uses cognitive change strategies to address mental health problems. Quality assessment of a CBT session is traditionally addressed by human raters who evaluate recorded sessions along specific behavioral codes, a cost prohibitive and time consuming method. In this work we examine how linguistic features can be effectively used to develop an automatic competency rating tool for CBT. We explore both standard, widelyused lexical features and domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 18 publications
2
23
0
Order By: Relevance
“…For example, Xiao et al (2015) found that the Support Vector Machines methods performed almost as well as trained coders. Similar results were reported in other studies (e.g., Flemotomos et al, 2018;Pérez-Rosas et al, 2019;Pérez-Rosas et al, 2017). Most studies only examined one type of method's performance.…”
Section: Article In Presssupporting
confidence: 88%
See 2 more Smart Citations
“…For example, Xiao et al (2015) found that the Support Vector Machines methods performed almost as well as trained coders. Similar results were reported in other studies (e.g., Flemotomos et al, 2018;Pérez-Rosas et al, 2019;Pérez-Rosas et al, 2017). Most studies only examined one type of method's performance.…”
Section: Article In Presssupporting
confidence: 88%
“…Pérez-Rosas et al, 2019 showed that as they increased the amount of data in their training set they observed significant improvement in prediction accuracy. Aligned with this finding, frequently observed codes (i.e., categories) in a dataset Howes et al, 2013;Perez-Rosas et al, 2017;Perez-Rosas et al, 2019;Xiao et al, 2015;Park et al, 2019;Flemotomos et al, 2018. Random Forest 7 Carcone et al, 2019Imel et al, 2015;Mieskes and Stiegelmayr, 2018;Blanchard et al, 2016a;Blanchard et al, 2016b;Donnelly et al, 2017;Wang et al, 2014.…”
Section: Article In Pressmentioning
confidence: 78%
See 1 more Smart Citation
“…We also adapted it using in-domain psychotherapy data. For role assignment, the two diarized speaker clusters were assigned to either therapist or client roles, following the method presented in [37]. Performance of this system was evaluated on additional psychotherapy sessions provided by the counseling center.…”
Section: Methodsmentioning
confidence: 99%
“…This body of work has focused primarily on identifying therapist skills in Motivational Interviewing, a highly structured psychotherapy approach used for resolving ambivalence related to the treatment of conditions such as substance or alcohol use, or to engaging with treatment in general (Miller and Rollnick, 2012). Independently, Flemotomos et al 2018 and Rojas Barahona et al 2018 applied machine learning approaches to code behaviors common in the context of Cognitive Behavior Therapy (CBT). Rojas Barahona et al developed neural network models for classification of various types of client 'thinking errors' identified as part of cognitive behavioral treatment, while Flemotomos et al built SVM models to classify the overall quality of a CBT treatment session, looking at the distribution of different types of therapist behaviors used within the session, both process and content-oriented (e.g.…”
Section: Related Workmentioning
confidence: 99%